Procedure for the assessment of R&D performance for a manufacturing company - Akçakaya, Reha (My University, 2001)
Araştırma-Geliştirme (Ar-Ge), sınai üreticiler için rekabet gücü elde etmenin en etkili araçlarından biri haline gelmiştir. Teknolojik değişimle başa çıkmak için teknolojik bilgiyi içselleştirip yeniden düzenleyebilmek, bunun için de özel bazı yetenekleri, donanımı ve yönetim tekniklerini geliştirmek gerekmektedir. Ar-Ge yatırımı yapan bütün sınai işletmelerin üst düzey yönetimleri, doğal olarak Ar-Ge yatırımlarının şirket karlılığına katkı sağlayıp sağlamadığı, ve şirket geleceğinin teknik anlamda garanti altında olup olmadığı ile çok yakından ilgilenmek durumundadırlar. Bu çalışma, endüstriyel Ar-Ge performansının değerlendirilmesi için yeni bir model önermektedir. Bu modelde yalnızca Ar-Ge'nin parasal katkıları değil, aynı zamanda parasal olmayan Ar-Ge çıktıları, Ar-Ge biriminin içinde bulunduğu dahili ve harici ortamın kalitesi, Ar-Ge faaliyetleri için ayrılmış olan varlıklar, ve Ar-Ge yönetiminin uygulamaya koyduğu yöntemler birlikte ele alınmaktadır. Bu şekilde, koşullar, ortaya konan çaba ve elde edilen sonuçlar birlikte değerlendirilerek üst yönetime sonuçlar ve süreçlerle ilgili sayısal ve sözel göstergeler sunulmaktadır.

Research and Development (R&D) is proven to be one of the most effective tools in the hands of manufacturing businesses for obtaining competitive power. Coping with rapid technological change needs special skills, hardware and management techniques to be able to absorb and modify technological knowledge. Top management of all industrial enterprises are naturally interested in knowing if their R&D investments are returned as increased profits, and if future of the company is technically secured by the long-term commitments of the R&D management and staff. The present work introduces a novel methodology for the assessment of R&D effectiveness for a manufacturing company. The model takes into account not only the tangible and intangible results of R&D activities, but also the internal and external R&D environment surrounding the corporate research unit and tangible and intangible assets provided by the company (conditions); and the methods adopted by the R&D management for improving R&D results (effort). The conditions, effort and resulting outcome are therefore evaluated simultaneously to generate a set of qualitative and quantitative indicators of the development of corporate R&D of the company.
Keywords: ARAŞTIRMA VE GELİŞTİRME (AR-GE)